MGIMO-UNIVERSITY MASTER’S DEGREE IN INTERNATIONAL RELATIONS ”INTERNATIONAL POLITICS AND TRANSNATIONAL BUSINESS” (Сравнительная политика)
MGIMO-University Master’s Degree in International Relations ”International Politics and Transnational Business”.